Multiple schedules with response interruption and redirection to reduce stereotypy in children with autism spectrum disorder: Generalization and social validity. (19th February 2023) - Callahan, Ashley E.; Sidener, Tina M.; DeBar, Ruth M.; Deshais, Meghan A.; Pane, Heather M.; Patil, Priya
Abstract: Although response interruption and redirection (RIRD) and multiple schedule arrangements have sometimes been shown to be effective in reducing stereotypy for individuals with autism spectrum disorder (ASD), important questions remain about optimal methods for facilitating generalization and social validity. In the current study, we sought to extend the literature on stereotypy treatment and MSAs in several ways. First, we programmed for generalization by conducting sessions with two exemplars of two different categories of activities (i.e., school work, toy play) and assessing generalization with novel exemplars and activities and during the participant's typical instructional program. Second, we used RIRD instructions that were contextual models of appropriate behavior relevant to each activity. Third, during the free access component of the multiple schedule, we used a child's play tent as a first step toward teaching participants to engage in stereotypy during private free time. For all three participants with ASD, stereotypy decreased quickly and substantially, with reductions generalizing to novel activities and contexts. An extensive social validity assessment with board‐certified behavior analysts indicated high social acceptability of the goals, procedures, and outcomes.